Piloting a Strengths-Based Intervention to Enhance the Quality of Life of Families Raising Children With Autism - Stoliaryk, Olha; Semigina, Tetyana (Social Welfare: Interdisciplinary Approach, 2022)
A strengths-based perspective puts the resources of individuals, families, communities, and their environments, rather than their deficit needs, problems and pathologies, at the center of the social work helping process. This research was aimed at evaluating the effectiveness of an intervention developed on the basis of an approach based on the strengths of families raising children with autism in improving the family life quality, strengthening its capacity, expanding their rights and possibilities, and enhancing resilience. The experimental intervention was carried out at the Educational and Rehabilitation Center for Children with Autism “Dovira” (Lviv, Ukraine) and consisted of 12 group meetings. It had one experimental group (30 people) and two control groups (60 people). The results of pre- and post-intervention surveys demonstrate the encouraging evidences of the effectiveness of the strength-based intervention program in social work with families raising children with autism, which indicates the possibility of its application in the family social work practice, in particular with families raising children with autism and other developmental disorders.